2018
DOI: 10.3390/ijms19123983
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Multimerin-2 and EMILIN-2 Expression in Gastric Cancer Associate with Altered Angiogenesis

Abstract: Gastric cancer is a deadly tumor and a relatively common disease worldwide. Surgical resection and chemotherapy are the main clinical options to treat this type of disease, however the median overall survival rate is limited to one year. Thus, the development of new therapies is a highly necessary clinical need. Angiogenesis is a promising target for this tumor type, however clinical trials with the use of anti-angiogenic drugs have so far not met expectations. Therefore, it is important to better characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 63 publications
(113 reference statements)
1
26
0
Order By: Relevance
“…EMILIN/Multimerins are a unique family of glycoproteins present in the extracellular matrix (Colombatti et al, 2012). Previous research demonstrated the role of EMILIN/ Multimerins in regulating tumor growth progression (Andreuzzi et al, 2018;Rabajdova et al, 2016) including the association of EMILIN3 in LGG survival rates (Zeng et al, 2018). LGG is a chronic disease characterized by tumor migration, infiltration of the brain's connectome and recurrence after conventional treatment (Delgado-Lopez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMILIN/Multimerins are a unique family of glycoproteins present in the extracellular matrix (Colombatti et al, 2012). Previous research demonstrated the role of EMILIN/ Multimerins in regulating tumor growth progression (Andreuzzi et al, 2018;Rabajdova et al, 2016) including the association of EMILIN3 in LGG survival rates (Zeng et al, 2018). LGG is a chronic disease characterized by tumor migration, infiltration of the brain's connectome and recurrence after conventional treatment (Delgado-Lopez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous research has reported that high expression of EMILIN3 was confirmed to predict poor survival in LGG (Zeng et al, 2018). Also, recent studies have confirmed that the appearance of Multimerin-2 and EMILIN-2 is significantly altered in gastric cancer patients (Andreuzzi et al, 2018) and EMILIN2 has a bidirectional role in tumor micro environments (Mongiat et al, 2010). Although EMILIN/Multimerins act as promising biomarkers in tumor development, heir expression pattern, molecular function and prognostic value in LGG have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…LGG (Zeng et al 2018). And, recent studies have confirmed that the appearance of Multimerin-2 and EMILIN-2 is significantly altered in gastric cancer patients (Andreuzzi et al 2018) and EMILIN2 has a bidirectional role in tumor microenvironments (Mongiat et al 2010). Although EMILIN/Multimerins act as promising biomarkers in tumor development, heir expression pattern, molecular function and prognostic value in LGG have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of 188 genetic alterations in EMILIN/Multimerins range from 0.4% to 1.4% for each member (EMILIN1 189 0.4%, EMILIN2 1.4%, EMILIN3 0.4%, MMRN1 0.4% and MMRN2 1.4%; Figure 8B). (Andreuzzi et al 2018;Rabajdova et al 2016) including the 224 association of EMILIN3 in LGG survival rates (Zeng et al 2018).…”
mentioning
confidence: 99%
“…EMILIN1, the most notable member of the EMILIN/Multimerin family, was overexpressed 230 in many organs, including blood vessels, lymphatic vessels, connective tissues, cardiovascular 231 system and the central nervous system (Modica et al 2017). The main functions of EMILIN1 232 include cell adhesion and migration in tumor growth (Capuano et al 2018). Modica, TME et 233 al (Modica et al 2017) founded that EMILIN1 can silences the RAS-ERK pathway via alpha4beta1 234 integrin, decreasing tumor cell growth.…”
mentioning
confidence: 99%